The Islamic Traditional Arts and the Traces of Science: A Study of Ethnomathematics in Ambe-Ambeken Dance in Aceh Singkil - Nur Ainun Lubis; Dharma Kelana Putra; Amrul Badri; Wahyu Wiji Astuti (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
This research explores the origins of the Ambe-ambeken Dance from Singkil Regency, the form of the Ambe-ambeken Dance, and analyzes the ethnomathematics. As a cultural entity, the Singkil people have a dance known as the Ambe-ambeken or Sakhindayong dance. This study uses a descriptive qualitative method to describe the Ambe-ambeken dance based on historical, anthropological and mathematical approaches. Although the variety of movements looks simple at first glance, this dance is a form of technology of enchantment that is full of wisdom and has an essential role in shaping the community's personality and the spread of Islam in Singkil through the poems that are sung during the dance. Then from a different perspective, it was found that there is a mathematical element that many people do not realize in a traditional dance, namely a geometric transformation. This fact leads to a new assumption that culture in the past was built on spirituality and aesthetic values and by applying mathematical principles in various aspects of life. Penelitian ini mengungkap asal-usul Tari Ambe-ambeken dari Kabupaten Singkil, bentuk Tari Ambe-ambeken serta menganalisis etnomatematika pada Tari Ambe-ambeken Sebagai sebuah entitas kultural, masyarakat Singkil memiliki sebuah tarian yang dikenal sebagai tari Ambe-ambeken atau Sakhindayong.. Penelitian ini menggunakan metode kualitatif deskriptif, yang bertujuan untuk mendeskripsikan tari ambe-ambeken berdasarkan pendekatan Sejarah, Antropologi dan Matematika. Meskipun sepintas ragam geraknya terlihat sederhana, tetapi tarian ini merupakan bentuk technology of enchantment yang sarat akan kearifan dan memiliki peranan penting dalam pembentukan kepribadian masyarakat serta penyebaran agama Islam di Singkil melalui syair-syair yang dibawakan selama tarian berlangsung. Kemudian dari sisi yang berbeda, ditemukan bahwa ada unsur matematika yang tidak disadari oleh banyak orang dalam suatu tarian tradisional, yakni berupa transformasi geometri. Fakta ini mengarahkan pada asumsi baru bahwa kebudayaan di masa lalu tidak hanya dibangun atas dasar spiritualitas dan nilai estetika semata, tetapi juga dengan menerapkan prinsip matematika dalam berbagai aspek kehidupan.